Using Ecopath Models to Explore Differences in Ecosystem Characteristics Between an Artificial Reef and a Nearby Natural Reef on the Coast of the North Yellow Sea, China - Zhang, Rongliang; Zhang, Qianqian; Zhao, Jianmin; Wu, Zhongxin; Liu, Hui; Shou, Lu; Liao, Yibo; Liu, Qinghe; Tang, Yanbin; Zeng, Jiangning (Frontiers in Marine Science, 2022)
The comparison of trophic structure and energy flow between natural and artificial reefs is imperative, to evaluate whether these man-made structures work similarly to comparable natural reefs. Here, to characterize the potential difference in functioning between two types of reef ecosystem, two trophic models (Ecopath) at an artificial reef and an adjacent natural reef in the coast of the north Yellow sea, China were established. Both Ecopath models were divided into 18 functional groups from primary producers (algae and phytoplankton) and detritus to predatory species (e.g. Sebastes schlegelii). Model outputs showed that ecosystem scale was smaller in the artificial reef (Total System Throughput, TPP = 6455.47 t·km-2·year-1) relative to its natural counterpart (TPP = 9490.48 t·km-2·year). At both reef types, function groups were clustered into four trophic levels, where a large amount of energy occurred at trophic levels I and II and most of the primary production was utilized through a detritus pathway. This result implies a bottom-up energy flow control for both cases. However, two types of reef systems were behaving in a reasonable manner, as mean transfer efficiencies were similar to the Lindeman efficiency (10%). The ecosystem maturity of the artificial reef is not comparable to that of the natural reef, for its inferior value of total primary production / total respiration (TPP/TR). Moreover, both the connectance index (CI) and system omnivory index (SOI) were slightly higher at the artificial reef relative to the natural reef as well as other coastal systems with parallel latitudes, suggesting that the current artificial system has formed complicated inter-species relations and high level stability. This work updates our knowledge about the functioning evolvement of established artificial reefs, and provides a baseline for the efficient management of coastal zones and further investigations.